Epidemiology and outcome of acute burn patients at a new dedicated burn centre in Nepal - Sudhin, Budhi Nath Adhikari; Adhikari, Sanjit; Khatiwada, Sushma (Journal of Society of Surgeons of Nepal, 2020)
Introduction: Burn injury remains one of the biggest health concerns in the developing world. It has been regarded as a formidable public health issue in terms of mortality, morbidity and permanent disability. We aim to provide an overview of the basic epidemiological characteristics of burn patients admitted at a dedicated burn center in Chitwan, Nepal. Methods: This was a retrospective, hospital-based observational study conducted at Chitwan Medical College Teaching Hospital (CMCTH) burn ward from September 2017 to August 2019. Patients’ records from admission/discharge book, admission/discharge summaries as well as patient’s individual files were reviewed to obtain the necessary data. Demographic data, clinical characteristics, treatments and outcomes were statistically analyzed. Results: Among the 202 patients, the number of males slightly predominated that of females with a ratio of 1.02:1. The median age was 24 years, and the median total body surface area (TBSA) burned was 15%. Children less than 10 years comprised one third of all patients while more than one fifth were elderly. The commonest etiological factor was flame burn, closely followed by scald. The mortality rate was 12.38% for the period under review. Majority of the patients spent less than 10 days on admission and around one fifth needed surgical intervention aimed at earlier coverage. Binary logistic regression analysis showed that age, Body Mass Index (BMI) and total body surface area (TBSA) burnt were the major predictors of burn mortality. Conclusions: The outcome of burn injuries is poor. Appropriate preventive & therapeutic measures need to be taken in terms of social education & provision of quality healthcare to reduce the incidence & improve the survival outcome of burn patients which should focus on children and elderly especially during the winter season.